A passivation solution and an environmentally friendly hot-dip galvanizing process using the same
By adding specific ingredients, such as organic acids, phosphates, modified nano-silica, etc. to the chromium-free passivation liquid, a stable and dense passivation film is solved, and the corrosion resistance and service life of the galvanized parts are significantly improved.
Patent Information
- Application Number
- CN202411987795.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing chromium-free passivation liquid coating has a short protection time and is unable to effectively improve the service life of galvanized parts.
A passivation liquid is used, and the components include organic acids, phosphates, modified nanosilica, cocamidopropyl betaine, modified polyacrylonitrile fiber, disodium ethylenediaminetetraacetate and potassium permanganate. Through the combination of these components, a stable and dense passivation film is formed to improve the corrosion resistance of the metal surface.
It significantly extends the protection time of the passivation film, improves the corrosion resistance and service life of the galvanized parts, and ensures the stability and efficiency of the passivation fluid.
Smart Images

Figure BDA0005222981090000091 
Figure BDA0005222981090000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of stainless steel surface treatment, and in particular to a passivation solution and an environmentally friendly hot-dip galvanizing process using the passivation solution. Background Art
[0002] Steel is prone to chemical or electrochemical reactions with oxygen, water, etc., which leads to the gradual destruction of the steel surface and the generation of rust. This rust will not only reduce the service life of steel, but also may affect its safety and reliability. Usually, galvanizing on the surface of steel improves the corrosion resistance of steel. The galvanized layer is prone to corrosion in a humid environment. In order to improve the corrosion resistance of the galvanized layer, passivation treatment is usually performed after galvanizing to improve the corrosion resistance of the galvanized parts and extend their service life.
[0003] Traditional passivation treatment uses chemical substances such as chromate for passivation treatment. This method may cause environmental pollution problems. Chromium-free passivation is accelerating the replacement of traditional chromate passivation technology. It uses chromium-free chemical substances for passivation treatment and can also generate a dense protective film on the surface of the galvanized layer.
[0004] The prior art uses nano-modified acrylic emulsion for galvanized sheet, the ingredients of which include water-soluble acrylic resin, nano-silica sol, dispersant, wetting agent and water. The treating agent uses water-based acrylic resin as a film-forming substance and adds nano-silica sol to form a high-density organic / inorganic hybrid film layer. However, the protection time of the coating is not long-lasting, the corrosion resistance protection time is short, and the service life needs to be improved. Summary of the invention
[0005] In order to improve the problem of short-lasting coating protection time and short corrosion protection time in chromium-free passivation solution, the present application provides a passivation solution and an environmentally friendly hot-dip galvanizing process using the passivation solution.
[0006] The present application provides a passivation solution, which adopts the following technical solution: A passivation solution comprises the following raw materials, measured by weight: 4-6 parts of organic acid, 8-10 parts of phosphate, 6-8 parts of modified nano silicon dioxide, 1-2 parts of cocamidopropyl betaine, 5-7 parts of modified polyacrylonitrile fiber, 1-2 parts of disodium ethylenediaminetetraacetate, 1-3 parts of potassium permanganate and 30-35 parts of deionized water.
[0007] By adopting the above technical scheme, the organic acid can react with the oxide on the metal surface during the passivation process to form a stable and dense passivation film, thereby protecting the metal from further corrosion. Phosphates not only play a role in stabilizing chemical reactions and help promote the film-forming process, but also can be used as a buffer to adjust the pH value of the passivation solution, prevent acid-base reactions from damaging the passivation film, and ensure the stability of the passivation solution. After the modified nano-silicon dioxide is added to the passivation solution, a colloidal solution is formed. After being applied to the metal surface and dried, the passivation solution will solidify into a gel, which has a strong adhesion to the metal surface; and the gel formed by the modified silicon dioxide itself also has a certain isolation effect, which can prevent external moisture and gas from penetrating into the metal surface, and play a certain auxiliary anti-corrosion role.
[0008] Cocoamidopropyl betaine has good foaming, conditioning and thickening effects, thus improving the foaming and stability of the passivation solution. Modified polyacrylonitrile fiber can enhance the density and adhesion of the film layer, and cooperate with modified nano-silica to improve the density and adhesion of the passivation film, making the passivation film more uniform and stable, thereby enhancing the corrosion resistance of the metal surface; it can also maintain the uniform dispersion of other components in the solution, prevent precipitation, and ensure the stability and efficiency of the passivation process. Disodium ethylenediaminetetraacetic acid forms a complex with metal ions and takes them away, effectively removing the metal ions in the outer layer of the passivation film, ensuring the density and stability of the passivation film. Potassium permanganate can oxidize impurities on the metal surface, promote the formation of the passivation film, and improve the density and corrosion resistance of the passivation film.
[0009] Preferably, the organic acid is one or more of citric acid, tartaric acid and phytic acid.
[0010] By adopting the above technical solution, citric acid can be used as a corrosion inhibitor to slow down the corrosion rate of the metal surface, prolong the passivation time and improve the passivation quality; it can also enhance the cleaning effect of the passivation solution and help remove dirt and oxide layers on the metal surface. Tartaric acid provides functional groups such as hydroxyl and carboxyl required for film formation, which helps to form a more stable and dense passivation film and improve the corrosion resistance of the passivation film. Phytic acid can form a strong and dense monomolecular protective film on the metal surface, inhibiting the oxidative corrosion of the metal, thereby improving its corrosion resistance.
[0011] Preferably, the preparation method of the modified nano-silicon dioxide comprises the following steps: (1) dispersing nano-silica in a sodium hydroxide solution, ultrasonically treating for 20-25 minutes, and then dispersing in a hydrochloric acid solution, ultrasonically treating for 25-30 minutes, washing, and activating at 160-170° C. for 1-2 hours to obtain pretreated nano-silica; (2) Dispersing the pretreated nano-silica in step (1) in deionized water, adding modified bentonite and xanthan gum, stirring evenly, stirring at 60-65° C. for 1-2 h, and drying to obtain modified nano-silica.
[0012] By adopting the above technical scheme, nano-silicon dioxide particles are dispersed in a sodium hydroxide solution, and the alkaline environment of sodium hydroxide is used to partially ionize the silanol (Si-OH) on the surface of the nano-silicon dioxide, thereby enhancing its dispersibility in the solution; and then dispersed in a hydrochloric acid solution to adjust the charge state of the surface of the nano-silicon dioxide in one step, thereby improving its compatibility with subsequent treatment steps. The nano-silicon dioxide is activated to remove adsorbed water and other volatile substances on its surface.
[0013] Modified bentonite has a special layered structure, stability, dispersibility and adsorption properties. When mixed with pretreated nano-silicon dioxide, the nanoparticles will be embedded in the interlayers or pores of the modified bentonite, enhancing the structural stability of the bentonite and improving the dispersibility of the nano-silicon dioxide, so that the interaction between the subsequently prepared passivation liquid and the metal substrate increases, and the adhesion between the passivation film and the metal surface is improved, which helps the passivation film not to fall off or peel off during long-term use. Xanthan gum has thickening and stability, which makes the nano-silicon dioxide and modified bentonite bonded stably, and makes the modified nano-silicon dioxide more evenly dispersed on the metal surface, thereby improving the passivation effect. At the same time, it enhances the stability of the passivation liquid and prevents it from deteriorating or failing during use.
[0014] Preferably, the mass ratio of the nano-silicon dioxide, modified bentonite and xanthan gum is 1:0.4-0.6:0.1-0.2.
[0015] By adopting the above technical solution, the mass ratio of nano-silicon dioxide, modified bentonite and xanthan gum is further limited within a certain range, the compactness, adhesion and stability of modified nano-silicon dioxide are improved, the nano-silicon dioxide particles are embedded in the interlayer or pores of the modified bentonite, and the xanthan gum has good film-forming and adhesion properties, so that the nano-silicon dioxide and the modified bentonite are stably bonded, and the tiny pores on the metal surface can be filled later to form a denser passivation film, improve its stability, and thus enhance the corrosion resistance of the metal surface. The combination of nano-silicon dioxide, modified bentonite and xanthan gum has a synergistic effect, which enhances the adhesion of the passivation film to the metal matrix and prevents the film from falling off in a corrosive environment; it helps the uniform distribution of the passivation liquid on the metal surface, reduces the situation of local excessive thickness or thinness, thereby forming a more uniform passivation film and improving the passivation effect.
[0016] Preferably, the preparation method of the modified bentonite comprises the following steps: dispersing the bentonite in anhydrous ethanol, stirring for 1-2 hours, filtering, calcining at 300-310°C for 3-4 hours, then dispersing in deionized water, adding sodium hexametaphosphate dispersant, silane coupling agent and hydroxyethyl cellulose, stirring evenly, and drying to obtain modified bentonite.
[0017] By adopting the above technical scheme, ethanol is first used to remove some impurities in bentonite, and then calcined to remove crystal water, organic pollutants, etc. in bentonite, while making its structure more loose and increasing its specific surface area, thereby improving its adsorption performance. Sodium hexametaphosphate, silane coupling agent and hydroxyethyl cellulose are added, and sodium hexametaphosphate can be adsorbed on the surface of bentonite particles, and particles are prevented from agglomerating by electrostatic repulsion or steric hindrance effect, thereby improving the dispersibility of bentonite in water. Silane coupling agent further changes the surface properties of bentonite particles, enhances its adsorption capacity for heavy metal ions and organic pollutants, and helps the subsequent treatment of the surface of steel substrate. Hydroxyethyl cellulose has good film-forming and dispersibility, improves the dispersibility of bentonite in water, and can also form a protective film between bentonite particles to prevent particles from agglomerating, which is helpful for subsequent application in modified nano-silicon dioxide, improves the combination of nano-silicon dioxide and modified bentonite, and helps improve the performance of passivation liquid.
[0018] Preferably, the method for preparing the modified polyacrylonitrile fiber comprises the following steps: (1) dispersing polyacrylonitrile fiber in hydrogen peroxide, stirring for 30-35 minutes, washing with water, and then dispersing in a potassium laurate aqueous solution, filtering, and drying to obtain pretreated polyacrylonitrile fiber; (2) soaking the pretreated polyacrylonitrile fiber obtained in step (1) in a modification solution, adding nano-titanium dioxide, stirring at a temperature of 70-75° C. for 2-3 hours, filtering, and drying to obtain modified polyacrylonitrile fiber; The modified liquid comprises: chitosan, acetic acid, deionized water, coconut oil fatty acid diethanolamide and gelatin.
[0019] By adopting the above technical scheme, the surface of the polyacrylonitrile fiber is treated with hydrogen peroxide, so that more active groups are formed on the surface, thereby improving the hydrophilicity of the polyacrylonitrile fiber. The washed polyacrylonitrile fiber is then dispersed in an aqueous solution of potassium laurate to further modify the surface of the polyacrylonitrile fiber and enhance the interface bonding force between the polyacrylonitrile fiber and other materials.
[0020] In the modified solution, chitosan has good biocompatibility and antibacterial properties, and can form a protective film on the surface of polyacrylonitrile fiber to enhance the antibacterial and biocompatibility of the fiber. The composite use of chitosan and gelatin improves the film-forming property and mechanical properties of the fiber, while giving the fiber good antibacterial properties. Acetic acid dissolves chitosan, allowing chitosan to be evenly dispersed in the solution and then evenly loaded on the fiber surface. Coconut oil fatty acid diethanolamide improves the wettability and dispersibility of the fiber, helps the uniform distribution of chitosan on the fiber surface, and enhances the lubricity and softness of the fiber.
[0021] The pretreated polyacrylonitrile fiber is immersed in the modification liquid, so that a protective film is formed on the surface of the polyacrylonitrile fiber, which increases the mechanical strength, adhesion and viscosity of the fiber, so that the modified polyacrylonitrile fiber forms a dense protective film on the surface of the steel substrate, so that it can be stably attached to the metal surface, has good chemical stability and high mechanical strength, can effectively resist the erosion of corrosive media, and improve the durability and service life of metal products. Nano-titanium dioxide has good antibacterial properties, dispersibility and stability, and can adhere to the surface of polyacrylonitrile fiber through the modification liquid, increase the dispersibility, antibacterial and stability of the polyacrylonitrile fiber, and is subsequently used in the passivation liquid to improve the antibacterial properties of the passivation liquid, enhance the stability and anti-corrosion ability of the passivation film, improve the dispersibility of the passivation liquid, and improve the optical properties of the metal surface.
[0022] Preferably, the mass ratio of the polyacrylonitrile fiber, the modified liquid and the nano-titanium dioxide is 1:8-10:0.3-0.5.
[0023] By adopting the above technical scheme, the mass ratio of polyacrylonitrile fiber, modified liquid and nano-titanium dioxide is further limited within a certain range, and the modified polyacrylonitrile fiber obtained has good adhesion, mechanical strength and stability. The polyacrylonitrile fiber can enhance the mechanical strength and toughness of the protective film in the passivation solution, provide additional physical support, prevent the protective film from breaking or falling off due to external force during use, and improve the wear resistance of the metal surface. Nano-titanium dioxide has antibacterial properties, dispersibility and stability, and can be loaded on the surface of polyacrylonitrile fiber. The modified liquid has film-forming properties and adhesion, which increases the adhesion between nano-titanium dioxide and polyacrylonitrile fiber. The use of polyacrylonitrile fiber, chitosan and nano-titanium dioxide produces a synergistic effect and enhances the protective effect of the passivation solution. The polyacrylonitrile fiber provides physical support, the modified liquid forms a protective film, and the nano-titanium dioxide enhances the antibacterial properties and the stability of the passivation film. Under the joint action, the corrosion resistance of the metal surface is improved, the protective effect of the passivation solution is enhanced, and more effective anti-corrosion protection is provided for metal products.
[0024] Preferably, the mass ratio of chitosan, coconut oil fatty acid diethanolamide and gelatin is 1:0.2-0.4:0.6-0.8.
[0025] By adopting the above technical scheme, the mass ratio of chitosan, coconut oil fatty acid diethanolamide and gelatin is further limited within a certain range, and the obtained chitosan has good film-forming property, adhesion and stability. Chitosan has good film-forming property and biocompatibility, gelatin improves the mechanical properties and stability of chitosan, coconut oil fatty acid diethanolamide improves the dispersibility and stability of the system, and at the same time enhances the film-forming property, making the composite film more uniform and dense. The mixing of chitosan, coconut oil fatty acid diethanolamide and gelatin produces a synergistic effect, which enhances the film-forming property, mechanical properties, antibacterial properties, compatibility, stability and biocompatibility of the system.
[0026] In a second aspect, the present application also provides a method for preparing a passivation solution, comprising the following steps: mixing an organic acid, a phosphate, modified nano-silica, cocamidopropyl betaine, modified polyacrylonitrile fiber, disodium ethylenediaminetetraacetic acid, potassium permanganate, and deionized water, stirring evenly to obtain a passivation solution.
[0027] By adopting the above technical solution, various components in the passivation solution are uniformly mixed to obtain a passivation solution with good film-forming property, strong corrosion resistance and good adhesion.
[0028] In a third aspect, the present application also provides an environmentally friendly hot-dip galvanizing process, comprising the following steps: (1) Place the steel substrate in the pickling solution and soak for 15-17 minutes to remove the oxide on the surface of the steel plate, wash with water, and set aside; (2) immersing the steel substrate of step (1) in a plating agent at a temperature of 60-62° C. for 3-4 minutes for later use; (3) immersing the steel substrate of step (2) in zinc solution for 120-130 seconds at a temperature of 460-470° C. for standby use; (4) Immerse the steel substrate of step (3) in the above passivation solution for 3-5 minutes.
[0029] By adopting the above technical solution, the steel substrate is pickled to remove the oxidized rust on the surface of the steel substrate, clean the surface of the steel plate, and provide a clean, oxide-free substrate for subsequent coating treatment.
[0030] Then it is immersed in the plating agent to form a uniform salt film on the surface of the steel substrate, which improves the wettability of the steel substrate with the molten alloy and prevents the surface of the steel substrate from being further oxidized during the hot dip plating process.
[0031] The steel substrate is then immersed in zinc liquid for galvanizing to form a zinc coating on the surface of the steel substrate. The zinc coating can provide good anti-corrosion protection and prevent further oxidation of the steel plate.
[0032] Finally, it is immersed in the passivation solution to form a passivation film on the surface of the zinc coating, which improves its corrosion resistance, prevents the zinc coating from forming white rust in a humid environment, and extends the service life of the steel substrate.
[0033] In summary, this application has the following beneficial effects: 1. In the present application, the modified nano-silicon dioxide is added to the passivation liquid to form a colloidal solution. After being applied to the metal surface and dried, the passivation liquid is solidified into a gel, which has a strong adhesion to the metal surface; and the gel formed by the modified silicon dioxide itself also has a certain isolation effect, which can prevent external moisture and gas from penetrating into the metal surface, and play a certain auxiliary anti-corrosion role.
[0034] 2. The modified polyacrylonitrile fiber in this application can enhance the density and adhesion of the film layer, and cooperate with the modified nano-silicon dioxide to jointly improve the density and adhesion of the passivation film, making the passivation film more uniform and stable, thereby enhancing the corrosion resistance of the metal surface.
[0035] 3. In the present application, disodium ethylenediaminetetraacetic acid forms a complex with metal ions and carries them away, effectively removing the metal ions in the outer layer of the passivation film and ensuring the density and stability of the passivation film. DETAILED DESCRIPTION
[0036] The present application is further described in detail below in conjunction with embodiments.
[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0038] Preparation example of modified nano-silica Preparation Example 1-1 The preparation method of modified nano silicon dioxide comprises the following steps: (1) dispersing 1.8 kg of nano-silica in 2.5 L of 6% sodium hydroxide solution, ultrasonicating for 25 min, and then dispersing in 2.7 L of 12% hydrochloric acid solution, ultrasonicating for 28 min, washing, and activating at 165° C. for 1.5 h to obtain pretreated nano-silica; (2) The nano-silica pretreated in step (1) was dispersed in 3.5 L of deionized water, and modified bentonite and xanthan gum were added. The mixture was stirred evenly, stirred at 65° C. for 2 h, and dried to obtain modified nano-silica.
[0039] The particle diameter of nano-silica is 20nm; The mass ratio of nano-silica, modified bentonite and xanthan gum is 1:0.6:0.1.
[0040] The preparation method of modified bentonite comprises the following steps: dispersing 1.6 kg bentonite in 2 L anhydrous ethanol, stirring for 2 h, filtering, calcining at 300° C. for 4 h, and then dispersing in 3 L deionized water, adding 0.2 kg sodium hexametaphosphate dispersant, 0.5 kg silane coupling agent kh550 and 0.8 kg hydroxyethyl cellulose, stirring evenly, and drying to obtain modified bentonite.
[0041] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified bentonite is added.
[0042] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), no xanthan gum is added.
[0043] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of nano-silicon dioxide, modified bentonite and xanthan gum is 1:0.4:0.2.
[0044] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of nano-silicon dioxide, modified bentonite and xanthan gum is 1:0.1:0.5.
[0045] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no silane coupling agent is added in the preparation method of the modified bentonite.
[0046] Preparation Example 1-7 The difference from Preparation Example 1-1 is that hydroxyethyl cellulose is not added in the preparation method of the modified bentonite.
[0047] Preparation example of modified polyacrylonitrile fiber Preparation Example 2-1 The preparation method of modified polyacrylonitrile fiber comprises the following steps: (1) dispersing 1.5 kg of polyacrylonitrile fiber in 2 L of 20% by mass hydrogen peroxide, stirring for 35 min, washing with water, and then dispersing in 1.8 L of 5% by mass potassium laurate aqueous solution, filtering, and drying to obtain pretreated polyacrylonitrile fiber; (2) soaking the pretreated polyacrylonitrile fiber obtained in step (1) in a modification solution, adding nano-titanium dioxide, stirring at a temperature of 75° C. for 3 hours, filtering, and drying to obtain modified polyacrylonitrile fiber;
[0048] Preparation of modified liquid: 8 kg chitosan, 1 kg acetic acid, 20 kg deionized water, 2 kg coconut oil fatty acid diethanolamide, and 3 kg gelatin were mixed to obtain a modified liquid.
[0049] The mass ratio of polyacrylonitrile fiber, modifying liquid and nano-titanium dioxide is 1:8:0.5 (the amount of modifying liquid is selected from the configured modifying liquid).
[0050] The mass ratio of chitosan, coconut oil fatty acid diethanolamide and gelatin is 1:0.3:0.7.
[0051] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modifying liquid is added.
[0052] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no nano titanium dioxide is added.
[0053] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of polyacrylonitrile fiber, modified liquid and nano-titanium dioxide is 1:10:0.3.
[0054] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of polyacrylonitrile fiber, modified liquid and nano-titanium dioxide is 1:5:0.9.
[0055] Preparation Example 2-6 The difference from Preparation Example 2-1 is that coconut oil fatty acid diethanolamide is not added to the modified liquid.
[0056] Preparation Example 2-7 The difference from Preparation Example 2-1 is that no gelatin is added to the modified liquid. Example
[0057] Example 1 A passivation solution comprises the following raw materials by weight: 6kg of organic acid, 8kg of phosphate, 6kg of modified nano-silicon dioxide, 1kg of cocamidopropyl betaine, 7kg of modified polyacrylonitrile fiber, 2kg of disodium ethylenediaminetetraacetic acid, 3kg of potassium permanganate and 30kg of deionized water.
[0058] The organic acid is citric acid, and the phosphate is potassium phosphate; The preparation method of the passivation solution comprises the following steps: mixing organic acid, phosphate, modified nano-silica, cocamidopropyl betaine, modified polyacrylonitrile fiber, disodium ethylenediaminetetraacetic acid, potassium permanganate and deionized water, stirring evenly to obtain a passivation solution; An environmentally friendly hot-dip galvanizing process comprises the following steps: (1) Place the steel substrate in 20 kg of pickling solution and soak for 16 minutes to remove the oxide on the surface of the steel plate, then wash with water for standby use; the pickling solution is 20% nitric acid, 5% hydrofluoric acid, and 75% water.
[0059] (2) immersing the steel substrate of step (1) in a plating agent at a temperature of 60° C. for 3 minutes for later use; (3) immersing the steel substrate of step (2) in zinc solution for 125 seconds at a temperature of 460° C. for standby use; (4) Immerse the steel substrate prepared in step (3) in the passivation solution prepared in the present application for 4 minutes.
[0060] The plating aid is composed of 15kg zinc chloride, 6kg hexadecyltrimethylammonium bromide, 13kg sodium phosphate, 40kg water and 12kg citric acid; the size of the steel substrate is 1.0m×0.9m×0.5m.
[0061] The modified nano-silica was prepared by using Preparation Example 1-1; and the modified polyacrylonitrile fiber was prepared by using Preparation Example 2-1.
[0062] Example 2 A passivation solution, which differs from Example 1 in that, by weight, it comprises the following raw materials: 4 kg of organic acid, 10 kg of phosphate, 8 kg of modified nano-silicon dioxide, 2 kg of cocamidopropyl betaine, 5 kg of modified polyacrylonitrile fiber, 1 kg of disodium ethylenediaminetetraacetic acid, 1 kg of potassium permanganate, and 35 kg of deionized water.
[0063] Example 3 A passivation solution, which is different from Example 1 in that the modified nano-silicon dioxide is prepared using Preparation Example 1-2.
[0064] Example 4 A passivation solution, which is different from Example 1 in that the modified nano-silicon dioxide is prepared using Preparation Examples 1-3.
[0065] Example 5 A passivation solution, which is different from Example 1 in that the modified nano-silicon dioxide is prepared using Preparation Examples 1-4.
[0066] Example 6 A passivation solution, which is different from Example 1 in that the modified nano-silicon dioxide is prepared using Preparation Examples 1-5.
[0067] Example 7 A passivation solution, which is different from Example 1 in that the modified nano-silicon dioxide is prepared using Preparation Examples 1-6.
[0068] Example 8 A passivation solution, which is different from Example 1 in that the modified nano-silicon dioxide is prepared using Preparation Examples 1-7.
[0069] Example 9 A passivation solution, which is different from Example 1 in that the modified polyacrylonitrile fiber is prepared using Preparation Example 2-2.
[0070] Example 10 A passivation solution, which is different from Example 1 in that the modified polyacrylonitrile fiber is prepared using Preparation Example 2-3.
[0071] Embodiment 11 A passivation solution, which is different from Example 1 in that the modified polyacrylonitrile fiber is prepared using Preparation Example 2-4.
[0072] Example 12 A passivation solution, which is different from Example 1 in that the modified polyacrylonitrile fiber is prepared using Preparation Example 2-5.
[0073] Embodiment 13 A passivation solution, which is different from Example 1 in that the modified polyacrylonitrile fiber is prepared using Preparation Examples 2-6.
[0074] Embodiment 14 A passivation solution, which is different from Example 1 in that the modified polyacrylonitrile fiber is prepared using Preparation Example 2-7.
[0075] Comparative Example Comparative Example 1 A passivation solution, which differs from Example 1 in that modified nano-silicon dioxide is not added.
[0076] Comparative Example 2 A passivation solution, which differs from Example 1 in that the modified nano-silicon dioxide is replaced by an equal amount of nano-silicon dioxide.
[0077] Comparative Example 3 A passivation solution, which differs from Example 1 in that modified polyacrylonitrile fiber is not added.
[0078] Comparative Example 4 A passivation solution, which differs from Example 1 in that the modified polyacrylonitrile fiber is replaced by an equal amount of polyacrylonitrile fiber.
[0079] Performance testing The passivation solutions prepared in Examples 1-14 and Comparative Examples 1-4 were used to treat the steel substrate according to the environmentally friendly hot-dip galvanizing process in Example 1, and the obtained steel substrate was tested for performance: (1) Antibacterial performance: Tested in accordance with GB / T2591-2003 “Test methods and antibacterial effects of antibacterial plastics”.
[0080] (2) Neutral salt spray test: According to GB / T 10125-1997, observe whether there are white corrosion products on the surface of the sample during the spraying process. When white rust appears on the surface of the sample, it means that the passivation film on the surface of the sample has failed, so as to evaluate the passivation corrosion resistance.
[0081] (3) Adhesion test: refer to GB / T5210-85 "Determination of coating adhesion - Pull-off method" for testing; (4) Stability test: After the passivation solution is placed at room temperature for 1 day, observe whether there is precipitation or agglomeration, and record the probability of precipitation or agglomeration, that is, the percentage of the number of precipitation or agglomeration in the total number of the test composition.
[0082] (5) Surface smoothness test: The steel substrates after film formation were placed on an M-2000 ring-block friction and wear tester to measure the dynamic friction coefficient of each passivation film. The test results are shown in Table 1.
[0083] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the passivation solution prepared in Examples 1-2 of the present application has a good cleaning effect for cleaning the steel plate. Among them, the sterilization rate of Example 1 is 99.8%, the average anti-white rust time is 576h, and the adhesion is 36.54N / cm 2 , stability 0.5%, dynamic friction coefficient 0.11. It shows that the steel plate cleaned with the passivation solution of the present application has a good sterilization rate and corrosion resistance, the prepared passivation solution has good adhesion and stability, the obtained steel plate surface has gloss and brightness, and the obtained passivation film has good density and corrosion resistance.
[0084] In the preparation methods of modified nano-silica in Examples 3-4, modified bentonite and xanthan gum are not added respectively, and the mass ratio of nano-silica, modified bentonite and xanthan gum is changed in Examples 5-6. As can be seen from Table 1, the test results of sterilization rate, salt spray resistance, adhesion, stability and surface smoothness of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding test performance of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1 and 5, indicating that the nano-silica particles are embedded in the interlayers or pores of the modified bentonite, and xanthan gum has good film-forming properties and adhesion, so that the nano-silica and modified bentonite are stably bonded, and the nano-silica, modified bentonite and xanthan gum cooperate with each other to enhance the adhesion of the passivation film to the metal substrate and prevent the film layer from falling off in a corrosive environment.
[0085] In the preparation methods of the modified bentonite of Examples 7-8, no silane coupling agent and hydroxyethyl cellulose are added respectively. As can be seen from Table 1, the test results of the sterilization rate, salt spray resistance, adhesion, stability and surface smoothness of Examples 7-8 are significantly worse than those of Examples 1-2, but better than those of Example 3, indicating that the silane coupling agent changes the surface properties of the bentonite particles, enhances its adsorption capacity for heavy metal ions and organic pollutants, and is helpful for the subsequent treatment of the surface of the steel substrate; hydroxyethyl cellulose has good film-forming and dispersibility, improves the dispersibility of bentonite in water, prevents particle agglomeration, is helpful for subsequent application in modified nano-silica, and helps to improve the performance of the passivation solution.
[0086] In the preparation method of modified polyacrylonitrile fiber in Examples 9-10, modifying liquid and nano-titanium dioxide are not added respectively, and the mass ratio of polyacrylonitrile fiber, modifying liquid and nano-titanium dioxide is changed in Examples 11-12. It can be seen from Table 1 that the test results of sterilization rate, salt spray resistance, adhesion, stability and surface smoothness of Examples 9-10 are significantly worse than those of Examples 1-2 and Example 11, while the corresponding test performance of Example 12 is better than that of Examples 9-10, but worse than that of Example 1 and Example 11, indicating that nano-titanium dioxide has antibacterial properties, dispersibility and stability, and can be loaded on the surface of polyacrylonitrile fiber. The modifying liquid has film-forming properties and adhesion, which increases the adhesion between nano-titanium dioxide and polyacrylonitrile fiber. The coordinated use of polyacrylonitrile fiber, chitosan and nano-titanium dioxide produces a synergistic effect, enhances the protective effect of the passivation liquid, improves the corrosion resistance of the metal surface, and provides more effective anti-corrosion protection for metal products.
[0087] Coconut oil fatty acid diethanolamide and gelatin are not added to the modified liquid of Examples 13-14. As can be seen from Table 1, the test results of sterilization rate, salt spray resistance, adhesion, stability and surface smoothness of Examples 13-14 are significantly worse than those of Examples 1-2, but better than those of Example 9, indicating that chitosan has good film-forming property and biocompatibility, gelatin improves the mechanical properties and stability of chitosan, and coconut oil fatty acid diethanolamide improves the dispersibility and stability of the system, while enhancing the film-forming property, making the composite film more uniform and dense, and subsequently improving the treatment effect of the steel substrate.
[0088] In Comparative Examples 1 and 3, modified nano-silica and modified polyacrylonitrile fiber are not added, respectively. As can be seen from Table 1, compared with Example 1, the test results of the sterilization rate, salt spray resistance, adhesion, stability, and surface smoothness of Comparative Examples 1 and 3 are significantly worse than those of Examples 1-2, indicating that the modified nano-silica is added to the passivation solution to form a colloidal solution. After being applied to the surface of the steel substrate and dried, the passivation solution will be solidified into a gel, which has a strong adhesion to the surface of the steel substrate, thereby improving the corresponding performance of the steel substrate; the modified polyacrylonitrile fiber can enhance the density and adhesion of the film layer, making the passivation film more uniform and stable, thereby enhancing the corrosion resistance of the metal surface.
[0089] In Comparative Examples 2 and 4, the modified nano-silica is replaced by an equal amount of nano-silica, and the modified polyacrylonitrile fiber is replaced by an equal amount of polyacrylonitrile fiber. It can be seen from Table 1 that compared with Example 1, the test results of the sterilization rate, salt spray resistance, adhesion, stability, and surface smoothness of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified nano-silica and modified polyacrylonitrile fiber of the present application have better protective effects, form a passivation film, and improve the density and corrosion resistance of the passivation film.
[0090] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A passivation solution, characterized in that: The invention comprises the following raw materials by weight: 4-6 parts of organic acid, 8-10 parts of phosphate, 6-8 parts of modified nano-silicon dioxide, 1-2 parts of cocamidopropyl betaine, 5-7 parts of modified polyacrylonitrile fiber, 1-2 parts of disodium ethylenediaminetetraacetic acid, 1-3 parts of potassium permanganate and 30-35 parts of deionized water.
2. A passivation solution according to claim 1, characterized in that: The organic acid is one or more of citric acid, tartaric acid and phytic acid.
3. A passivation solution according to claim 1, characterized in that: The preparation method of the modified nano-silicon dioxide comprises the following steps: (1) dispersing nano-silica in a sodium hydroxide solution, ultrasonically treating for 20-25 minutes, and then dispersing in a hydrochloric acid solution, ultrasonically treating for 25-30 minutes, washing, and activating at 160-170° C. for 1-2 hours to obtain pretreated nano-silica; (2) Disperse the nano-silica pretreated in step (1) in deionized water, add modified bentonite and xanthan gum, stir evenly, stir at 60-65° C. for 1-2 h, and dry to obtain modified nano-silica.
4. A passivation solution according to claim 3, characterized in that: The mass ratio of the nano silicon dioxide, modified bentonite and xanthan gum is 1:0.4-0.6:0.1-0.
2.
5. A passivation solution according to claim 3, characterized in that: The preparation method of the modified bentonite comprises the following steps: dispersing the bentonite in anhydrous ethanol, stirring for 1-2 hours, filtering, calcining at 300-310° C. for 3-4 hours, then dispersing in deionized water, adding sodium hexametaphosphate dispersant, silane coupling agent and hydroxyethyl cellulose, stirring evenly, and drying to obtain the modified bentonite.
6. A passivation solution according to claim 1, characterized in that: The preparation method of the modified polyacrylonitrile fiber comprises the following steps: (1) dispersing polyacrylonitrile fiber in hydrogen peroxide, stirring for 30-35 minutes, washing with water, and then dispersing in a potassium laurate aqueous solution, filtering, and drying to obtain pretreated polyacrylonitrile fiber; (2) soaking the pretreated polyacrylonitrile fiber obtained in step (1) in a modification solution, adding nano-titanium dioxide, stirring at a temperature of 70-75° C. for 2-3 hours, filtering, and drying to obtain modified polyacrylonitrile fiber; The modified liquid comprises: chitosan, acetic acid, deionized water, coconut oil fatty acid diethanolamide and gelatin.
7. A passivation solution according to claim 6, characterized in that: The mass ratio of the polyacrylonitrile fiber, the modified liquid and the nano-titanium dioxide is 1:8-10:0.3-0.
5.
8. A passivation solution according to claim 6, characterized in that: The mass ratio of the chitosan, coconut oil fatty acid diethanolamide and gelatin is 1:0.2-0.4:0.6-0.
8.
9. The method for preparing a passivation solution according to claim 1, characterized in that: The method comprises the following steps: mixing organic acid, phosphate, modified nano silicon dioxide, cocamidopropyl betaine, modified polyacrylonitrile fiber, disodium ethylenediaminetetraacetic acid, potassium permanganate and deionized water, stirring evenly, and obtaining a passivation solution.
10. An environmentally friendly hot-dip galvanizing process, characterized in that: The steps include: (1) Place the steel substrate in the pickling solution and soak for 15-17 minutes to remove the oxide on the surface of the steel plate, wash with water and set aside; (2) Immerse the steel substrate prepared in step (1) in a plating agent at a temperature of 60-62° C. for 3-4 minutes and set aside; (3) immersing the steel substrate of step (2) in zinc solution for 120-130 seconds at a temperature of 460-470° C. for standby use; (4) Immerse the steel substrate of step (3) in the passivation solution of any one of claims 1 to 9 for 3 to 5 minutes.
Citation Information
Cited By
Galvanized steel with high toughness and preparation method thereof
CN121674875A